(untitled) (Journal of the Sociology and Theory of Religion, 2020)
The purpose of this work is to study the female dress of fallera and its impact on the Valencian festivities called Fallas. Currently, the fallera suit is between tradition and modernity, between the sacred and the profane, since it has been used as an idiosyncratic element to enlarge the Valencian people, also, it is still maintained as inspiration for creative and contemporary designers. Likewise, we must stop at the Valencian sedera manufacturing, since Valencia became in the 18th century the main center of silk production in the peninsula at the expense of Toledo. The monarchy contributed to the realization of a mercantilist production policy and the promotion of national textile manufacturing. Silk and its decoration were one of the most important modern manufactures, which until today are still present in popular festivities.